2018
DOI: 10.1002/acr.23348
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Toe Flexor Muscles in Older Adults With Toe Deformities

Abstract: This is the first study to use ultrasound to investigate the size of the toe flexor muscles in older adults with hallux valgus and lesser toe deformities compared to otherwise healthy older adults. The sizes of the abductor hallucis and flexor hallucis brevis muscles were decreased in participants with hallux valgus, whereas the quadratus plantae, flexor digitorum brevis, abductor hallucis, and flexor hallucis brevis muscles were smaller in the participants with lesser toe deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…In line with our hypothesis, we found that the AbH and FHB thickness and cross-sectional area were lower in individuals with HV compared to control group. Similar to our results, previous studies reported that individuals with HV had lower AbH and FHB cross-sectional area and thickness compared to healthy control 12, 13, 14. The results of the present study show that muscle strength of AbH and FHB muscles decrease in individuals with HV, because muscle size is an important determinant of muscle strength 9 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with our hypothesis, we found that the AbH and FHB thickness and cross-sectional area were lower in individuals with HV compared to control group. Similar to our results, previous studies reported that individuals with HV had lower AbH and FHB cross-sectional area and thickness compared to healthy control 12, 13, 14. The results of the present study show that muscle strength of AbH and FHB muscles decrease in individuals with HV, because muscle size is an important determinant of muscle strength 9 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast with our results, Lobo et al 13 reported that PF thickness is increased in individuals with HV, while FDB thickness and cross-sectional area are similar in with and without HV. Mickle et al 12 found that FDB thickness and cross-sectional area were similar in individuals with HV compared with those without HV. Increase in FDB thickness and cross-sectional area may be a compensation or adaptation against mechanical changes in foot and decreased intrinsic muscle strength associated with HV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zato ojačavanje unutarnjih mišića nožnih prstiju može pomoći smanjiti incidenciju i ozbiljnost deformacija stopala starijih osoba [9]. Cipele i ulošci trebaju biti u skladu s oblikom stopala korisnika tako da ne stišću i pritišću bilo koji dio stopala [10].…”
Section: Uvodunclassified
“…Therefore, strengthening the intrinsic toe muscles may help reduce the incidence and severity of toe deformities in older adults [9]. Shoes and insoles need to conform to the wearer's foot shape without squeezing or pressing any part of the foot [10].…”
Section: Introductionmentioning
confidence: 99%